ANALISIS ASAM RETINOAT PADA KOSMETIK KRIM PEMUTIH YANG BEREDAR DI PASARAN KOTA MANADO - Suhartini, Siti; Fatimawali, Fatimawali; Citraningtyas, Gayatri (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT Cosmetic whitening is a cosmetic that contains the active ingredient intended to bleach and brighten the skin or whiten the skin. Retinoic acid is used in whitening creams but is prohibited because it can cause dry skin, burning, and teratogenic (defects in the fetus). The purpose of this study was to determine whether whitening creams circulating in the city of Manado contains retinoic acid and to determine the levels of retinoic acid whitening cream found on the face. The samples studied were lightening cream sample A, sample B, sample C, sample D and sample E. The qualitative identification of retinoic acid have been done with Thin Layer Chromatocraphy (TLC) it has been given the dark blood if seen in UV spectrum 254 nm. Quantitative analysis was done by UV spectrophotometric maximum wavelength of 352 nm. The results indicated that three of sample contaided retinoic acid. Retinoic acid concentration in sample C was 0,021%, sample D was 0,026%, sample E was 0,016% and product retinoic acid cream (Vitacid) was 0,053%. Key words :Â Retinoic acid, Cosmetic whitening, Thin Layer Chromatocraphy (TLC), UV spectrophotometric.